Public expenditures, private incentives, and technology adoption: The economics of hybrid rice in South Asia - Spielman, David J.; Kolady, Deepthi; Ward, Patrick S.; Ar-Rashid, Harun; Gulati, Kajal (International Food Policy Research Institute, 2012)
The rapid expansion of hybrid rice cultivation in China has contributed significantly to improving food security in the country since the 1980s. However, few other Asian countries have seen similar expansions in hybrid rice cultivation or the associated yield and output gains. This paper examines the technical challenges, market opportunities, and policy constraints related to hybrid rice in South Asia, with specific emphasis on India and Bangladesh. The paper sets the discussion within a novel analytical approach to agricultural science, technology, and innovation that focuses on improving the efficiency with which new technologies are transformed into economically relevant products and services.